6-3(2x-1)=19+6x

Simple and best practice solution for 6-3(2x-1)=19+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3(2x-1)=19+6x equation:



6-3(2x-1)=19+6x
We move all terms to the left:
6-3(2x-1)-(19+6x)=0
We add all the numbers together, and all the variables
-3(2x-1)-(6x+19)+6=0
We multiply parentheses
-6x-(6x+19)+3+6=0
We get rid of parentheses
-6x-6x-19+3+6=0
We add all the numbers together, and all the variables
-12x-10=0
We move all terms containing x to the left, all other terms to the right
-12x=10
x=10/-12
x=-5/6

See similar equations:

| 7|2x-6|-4=10 | | 5n+3=2+6n-3 | | -7a-10=2–3a | | -5x-6x=x | | 9g-10=10g-10 | | 3(1-6n)-3(4-5n)=1-7n+3n+5 | | -1x+1=-3 | | F(x)=-x-4-1 | | 5x+3(.002)=1950 | | 7-4j+7=-2-8j | | -5-b=9+b | | 3x2+12x=7 | | 9g−10=10g−10 | | 18-(-8j)=-14 | | 18-x=33 | | 7b=10+9b | | 1x+3=5(x+4) | | 7/9t=1/4 | | 15=8+3b | | m/3=2+7 | | x-5/7=x-6/11 | | 10+9q=3q-8+9q | | -4x+-12=-32 | | 11x+1+37=7x+8 | | 1x+5=3(x+2) | | A=9m^2 | | 85y+20=17y-4 | | 2x-2+7x=16 | | 3u-10=-7u | | -1+5w=7w-9 | | -20=-8p-2p | | 5×+11y=26 |

Equations solver categories